2010
DOI: 10.1111/j.1469-0691.2010.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro activities of tetracyclines, macrolides, fluoroquinolones and clindamycin against Mycoplasma hominis and Ureaplasma ssp. isolated in Germany over 20 years

Abstract: Antimicrobial resistance in genital mycoplasmas is increasing and shows global variation. We determined the susceptibilities of 469 mycoplamas, comprising 290 Mycoplasma hominis and 179 ureaplasma isolates collected during 1983 and 1989-2004, to eleven antibacterials by agar dilution. Additionally, we analyzed the results of routine E-testing during 2005-2008. Doxycycline was the most active tetracycline with (MIC₉₀ of 1 and 8 mg/L for ureaplasmas and M. hominis, respectively. Significantly more M. hominis iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 27 publications
4
46
3
1
Order By: Relevance
“…In Hungary, in isolates collected between May 2008 and July 2010, 6.07 % (15/247) and 11.54 % (3/26) of U. urealyticum and M. hominis isolates were resistant to tetracycline, respectively (Farkas et al, 2011). Similar rates of tetracycline resistance were obtained in Germany according to a study involving 469 mycoplasma isolates (179 ureaplasmas and 290 M. hominis) collected over a 20-year period (Krausse & Schubert, 2010), with observed tetracycline resistance rates of 1-3 and 10-13 %, respectively. However, higher tetracycline resistance rates of U. urealyticum isolates (17 %) were reported in China (Zhou et al, 2011), and the 45 % (45/100) prevalence of tet(M) in ureaplasma isolates collected from a broad geographical area of the USA between 2000 and 2004 (Waites et al, 2005) suggests resistance rates even higher than those reported in Tunisia.…”
Section: Discussionsupporting
confidence: 56%
“…In Hungary, in isolates collected between May 2008 and July 2010, 6.07 % (15/247) and 11.54 % (3/26) of U. urealyticum and M. hominis isolates were resistant to tetracycline, respectively (Farkas et al, 2011). Similar rates of tetracycline resistance were obtained in Germany according to a study involving 469 mycoplasma isolates (179 ureaplasmas and 290 M. hominis) collected over a 20-year period (Krausse & Schubert, 2010), with observed tetracycline resistance rates of 1-3 and 10-13 %, respectively. However, higher tetracycline resistance rates of U. urealyticum isolates (17 %) were reported in China (Zhou et al, 2011), and the 45 % (45/100) prevalence of tet(M) in ureaplasma isolates collected from a broad geographical area of the USA between 2000 and 2004 (Waites et al, 2005) suggests resistance rates even higher than those reported in Tunisia.…”
Section: Discussionsupporting
confidence: 56%
“…Other two macrolides that were studied-azithromycin and erythromycin -were only moderately effective [32]. Resistance to erythromycin has been reported additionally by Ponyai et al [31] and Krausse et al [33] who determined that the resistance of ureaplasmas to erythromycin is 81% and 21%, respectively. Pignanelly et al [5] studied M. hominis and found that the isolates were sensitive to tetracycline and doxycycline but resistant to fluoroquinolones and macrolides except jocamycin.…”
Section: General Treatmentmentioning
confidence: 95%
“…Nevertheless, doxycycline is still the drug of choice for the treatment of urogenital mycoplasma infections and may also be used for coinfection with M. hominis [33]. However, resistant strains are increasingly prevalent.…”
Section: General Treatmentmentioning
confidence: 99%
See 2 more Smart Citations